Produksi etanol pada media pyg dengan variasi suhu dan perbandingan media fermentasi menggunakan isolat IS258 - Jamas Prameshwari; I Made Mahaputra Wijaya; Ida Bagus Wayan Gunam (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Bioethanol is produced by the fermentation of glucose (sugar) from natural sources using microorganisms. Prior isolate IS258 was distinguished as a potential yeast to produce bioethanol. This study aimed to determine the optimum fermentation temperature and compare fermentation media using IS258 isolate as a starter to produce ethanol optimally. This study conducted four fermentation temperature treatments (24, 26, 28, and 30 °C) and compared two fermentation media, namely, PYG (Peptone Yeast Glucose) media used in the lab for probed, and coconut sap in traditional fermentation. There are diverse stages that were conducted in this research, namely cell rejuvenation, propagation of the IS258 isolate, fermentation, distillation, and calculation of tested variables. The optimum temperature of fermentation acquires at 28 °C with a difference of total dissolved solids 12,4 ⸰brix, which attains 104,13 ml of accumulated ethanol. During the comparison test of fermentation media, the optimum PYG media produced the highest total ethanol, which was 105,46 ml. The difference in the total yield of ethanol is affected by the differences in the nutrients of carbon (C) and nitrogen (N) elements contained between the media, which was lacking in coconut sap